Cost Analysis of Monitoring Asthma Treatment using Sputum Cell Counts - Liesel D’silva; Amiram Gafni; Lehana Thabane; Lata Jayaram; Pat Hussack; Frederick E Hargreave; Parameswaran Nair (Canadian Respiratory Journal)
BACKGROUND: In a four-centre trial, the use of sputum cell counts (sputum strategy [SS]) to guide treatment had resulted in fewer and less severe exacerbations without the need for a higher corticosteroid dose, compared with the use of symptoms and spirometry (clinical strategy [CS]).